Revealing Medan's Chinese Ethnic Identity in Advertising Grief at Harian Analisa Newspaper - Agung Suharyanto; Taufik Wal Hidayat (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The purpose of this paper is to reveal the mass media and commodity relations of death to the Medan Chinese in the advertisement of mourning in the Harian Analisa   newspaper. The method used in this study was descriptive to reveal the mass media and commodity relations of death to Chinese ethnic in Medan in the advertisement of mourning in the daily newspaper The analisa was clear. Data obtained from the results of direct interviews with speakers are qualitative data used to answer the research objectives. The results obtained were Mass Media and the Relationship of Death Commodities to Chinese Ethnicity in Condolence Advertisements in Harian Analisa   Newspapers in Medan are two things that are closely related to respect for ancestors as well as the economy. These two activities were embodied by the Harian Analisa   Newspaper managed by Chinese people. The Grief Advertisements in Harian Analisa  , became one of the Chinese Ethnic identity markers in Medan, which distinguishes it from other ethnicities in Medan City. There are two types of death advertisements, namely Grief News and Grief. Anatomy of Grief Ads: Headline; Sub Headline; Name; Bodycopy; Family name; Photos and Frames. Chinese Ethnic Identity, seen from the presence of Condolence Advertisements in Harian Analisa   Newspaper as one of the teachings that the brand is still doing to Repay Budi to People Who Ever Helped; Maintain Closer Kinship in the family; Social Bonding and Togetherness, Cultural Defense and Respect for Ancestors.